Influence of Operational Costs on Operating Revenue and Loan to Deposit Ratio against Return on Asset at PT. Bank Negara Indonesia, Tbk Year 2009-2019 - Waluyo Jati (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the operational costs operating income (BOPO) and Loan to Deposit Ratio (LDR) on Return on Assets at PT. Bank Negara Indonesia, Tbk. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Operational Costs Operational Income (BOPO) has a significant effect on Return on Assets by 40.7%, hypothesis testing is obtained t count> t table or (2.346> 2.262). Loan to Deposit Ratio (LDR) has a significant effect on Return on Assets of 53.9%; hypothesis testing is obtained t count> t table or (-3.056> -2.262). Operating Costs Operational Income (BOPO) and Loan to Deposit Ratio (LDR) simultaneously have a significant effect on Return on Assets, the regression equation Y = 1.565 + 0.205X1 - 0.089X2 and a determination value of 59.9%, hypothesis testing obtained the F value calculated > F table or (5,224> 4,350).